A Study on Prevalence and Correlates of Functional disability among the elderly in rural Tamilnadu - Sowmiya, KR.; Kumar, P.Ganesh; Nagarani, Nagarani (International Journal of Medical Research and Review, 2015)
Introduction: Functional status assessment is fundamental to geriatric care. Hence this study was done to know the prevalence of functional disability among the elderly aged 60 years and above residing in a rural area of Tamilnadu and to identify the socio demographic and health correlates that influence their functional status. Methodology: This cross sectional study was done among elderly members residing in a rural part of Tamilnadu. Functional status of the study population - vision, hearing, arm function, leg function, cognition and Activities of Daily Living (ADL) were assessed. Results: The prevalence of functional disability among the elderly aged 60 years and above was found to be 46.84%.Visual impairment was the most commonly observed functional defect with 34% of female and 21.6% of male elderly being affected. 27.3% of female elders were dependent for doing their Activities of Daily Living. Hearing impairment was also common with 16.4% and 28.7% of male and female elders being affected respectively. The prevalence of functional disability was very high with advancing age, presence of co morbidities, illiteracy and economical dependence. The prevalence of functional disability was low among the male elderly and those who lived with their spouse and children. Conclusion: This study emphasizes the need for assessing the functional status of the elderly population at primary health care level to determine their needs, develop interventions to restore or maintain function or prevent or minimize its decline, and prevent secondary disabilities